Zredukuj wyrazy podobne , a następnie oblicz wartość wyrażenia.

a) x = 2 1/2 y=1,2
4 (3x + 2y) - (8x + 3y) + 6 =

b) x = 2,5 y = -1
2y - (6x + 3y) + 2 (x+3) =

c) x = -6 y = -4
-2 ( 1/2 + 1 1/5x) + (-1/3 + 1 1/5x + y) =

d) x= 1/6 y= 1/12

-(3x) + (2x - 3y + 2/3 ) - (x +y) =

e) x =5 y = -2
- (2x+1) + (3x + 2 ) - (x-y) =

mogę prosić o pomoc? ..
najlepiej z obliczeniami..
bd wdzięczna..

2

Odpowiedzi

2010-02-16T19:43:14+01:00
A) 4(3x + 2y) - (8x + 3y) + 6 =4×(7 1/2 + 2 2/5) - 20 - 3.6 = 30 + 9.6 - 20 - 3.6 = 16
b) -2 - 15 + 3 + 5 + 6 = -3
c) -1 + 14.4 - 1/3 - 7.2 -4 = 1,2
d) -1/2 + 1/3 - 1/4 +2/3 - 1/6 - 1/12 = -6/12 + 4/12 - 3/12 + 8/12 - 2/12 - 1/12 = 0
e) -10 - 1 + 15 + 2 -5 + 2 = 3
Najlepsza Odpowiedź!
2010-02-16T19:50:28+01:00
A) x = 2 1/2 y=1,2
4 (3x + 2y) - (8x + 3y) + 6 =12x+8y-8x-3y+6=12x-8x+8y-3y+6=
=4x+5y+6=4*2½+5*1,2+6=10+6+6=22

b) x = 2,5 y = -1
2y - (6x + 3y) + 2 (x+3) =2y-6x-3y+2x+6=2y-3y-6x+2x+6=
=-y-4x+6=-(-1)-4*2,5+6=1-10+6=-3

c) x = -6 y = -4
-2 ( 1/2 + 1 1/5x) + (-1/3 + 1 1/5x + y) =-2(½+⁶/₅x)+(-⅓+⁶/₅x+y)=
=-1-2,4x-⅓+⁶/₅x+y=-2,4x+⁶/₅x+y-1-⅓=-²⁴/₁₀x+⁶/₅+y-³/₃-⅓=
=-²⁴/₁₀x+¹²/₁₀+y-⁴/₃=-¹²/₁₀x+y-⁴/₃=-¹²/₁₀*(-6)+(-4)-⁴/₃=
=⁷²/₁₀-4-⁴/₃=7,2-4-1,33≈1,87

d) x= 1/6 y= 1/12
-(3x) + (2x - 3y + 2/3 ) - (x +y) =-3x+2x-3y+²/₃-x-y=
=-3x+2x-x-3y-y+²/₃=-2x-4y+²/₃=-2*¹/₆-4*¹/₁₂+²/₃=
=⅓-⅓+²/₃=²/₃

e) x =5 y = -2
- (2x+1) + (3x + 2 ) - (x-y) =-2x-1+3x+2-x+y=
=-2x+3x-x+y-1+2=y+1=-2+1=-1